1992
DOI: 10.1007/bf00711325
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofN‐acetyl‐α‐aminoadipic acid in the urine of a patient with α‐aminoadipic and α‐ketoadipic aciduria

Abstract: A 3.5-year-old Japanese boy with a mild speech disturbance excreted a large amount of alpha-aminoadipic acid into the urine. The amino acid analysis using an amino acid analyser confirmed the presence of alpha-aminoadipic acid in both urine and plasma. We detected alpha-aminoadipic acid in the hydrolysate of the effluent and washwater fraction through cation exchange resin. This suggested the presence of acetylated derivatives and we identified N-acetyl-alpha-aminoadipic acid using liquid chromatography-atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A defect in the alpha-ketoadipic acid (KAA) dehydrogenase complex causes the increased urinary excretion of KAA and alphaaminoadipic acid (AAA). In addition, patients may display increased urinary excretion of alpha-hydroxyadipic acid (HAA) and N-acetyl-AAA (Takechi et al 1993), and elevated levels of plasma AAA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A defect in the alpha-ketoadipic acid (KAA) dehydrogenase complex causes the increased urinary excretion of KAA and alphaaminoadipic acid (AAA). In addition, patients may display increased urinary excretion of alpha-hydroxyadipic acid (HAA) and N-acetyl-AAA (Takechi et al 1993), and elevated levels of plasma AAA.…”
Section: Introductionmentioning
confidence: 99%
“…Following these initial findings, alpha-aminoadipic aciduria often with alpha-ketoadipic aciduria has been diagnosed mainly in individuals with mental retardation. Other reported symptoms are moderate metabolic acidosis , seizures (Casey et al 1978;Manders et al 1981;Duran et al 1984), obesity (Casey et al 1978), immunodeficiency (Gray et al 1979), dysmorphic features (Manders et al 1981), hypotonia with delayed motor development Vianey-Liaud et al 1985), mild speech retardation (Takechi et al 1993), episodic vomiting (Sewell et al 1999), apnea due to gastroesophageal reflux and tremor (Sewell et al 1999). At the same time, a causal relationship between the biochemical abnormality and the clinical findings has been questioned ever since the identification of the first patient.…”
Section: Introductionmentioning
confidence: 99%
“…α-ketoadipic aciduria was first described by Przyrembel et al in 1975 since then 7 cases have been reported [1][2][3][6][7][8][9] using GC/MS or other analytical methods, and some subjects with α-ketoadipic aciduria were found by reexamination [3] . In addition to symptomatic cases, 6 asymptomatic cases have also been reported [2][3][4][5]10] .…”
Section: Discussionmentioning
confidence: 99%
“…α-ketoadipic aciduria (Mckusick 245130) is a rare inborn error in the metabolism of α-KA to glutaryl-CoA and is characterized by the increased excretion of α-KA, α-aminoadipate (α-AA) and α-hydrocyadipate (α-HAA). Since Przyrembel et al firstdescribed it in 1975 [1] , only 13 cases of α-ketoadipic aciduria have been reported over the past 25 years, including 7 symptomatic, and 6 asympotmaticones even in the symptomatic siblings with α-ketoadipic aciduria [1][2][3][4][5][6][7][8][9][10] . The clinical manifestations of this metabolic disorder showed heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…a-ketoadipic aciduria (McKusick 245130), first described by Przyrembel et al in 1975 (1), is an inborn error of metabolism caused by a defect in the oxidative decarboxylation of 2-oxoadipate, a catabolic intermediate of lysine, tryptophan and hydroxylysine, to glutaryl-CoA. Since 1975, twelve cases of a-ketoadipic aciduria from eight families have been described (1)(2)(3)(4)(5)(6)(7)(8)(9). Due to the clinical heterogeneity of cases with a-ketoadipic aciduria, it might be that mass screening for this disease has not been considered useful because it is difficult to judge whether or not the neonates with a-ketoadipic aciduria should be diagnosed and treated at their early stages.…”
mentioning
confidence: 99%